Effect of interfacial fibre orientation and PPS veil density on delamination resistance of 5HS woven CFRP laminates under mode II loading. (3rd May 2021) - Ramji, Amit; Xu, Yigeng; Grasso, Marzio; Yasaee, Mehdi; Webb, Philip
Abstract: This paper presents an experimental study on the effect of interfacial fibre orientation and interleaved thermoplastic veil on Mode II interlaminar fracture toughness of 5-harness satin woven carbon fibre reinforced polymer composite laminates. Three-point End-Notched Flexure tests were carried out to determine delamination resistance, GIIC, of specimens with five fibre orientation biases and two veil densities at the midplane. Results show that delamination resistance of 5-harness satin woven laminates depends on the layup configurations at the midplane with 90/45 fibre orientation bias exhibiting the greatest resistance. The delamination resistance enhancement from polyphenylene sulfide (PPS) veil interleaves is also fibre orientation dependent but a further increase of the veil density from 10 gm −2 to 20 gm −2 offers little extra benefit. Fracture surface morphologies were examined under SEM to understand the failure mechanism and fracture process of the woven laminate under the combined effects of the interfacial fibre orientation and the veil density. Fibre orientation relative to the delamination path, surface texture misfit, and veil density are the three main contributors identified for the variation of delamination resistance of 5HS woven laminates. Graphical abstract: Image 1 Highlights: Fibres at an angle to the delamination path improve delamination resistance. Texture misfit facilitates formation of resin rich zones and reduce delamination resistance. Thermoplastic veil improves the delamination resistance but the effect if quickly saturated. Test standard suitable for GIIC measurement of woven laminates is highly desirable.